2018
DOI: 10.1089/nat.2017.0703
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Frataxin Protein Expression by Antisense Oligonucleotides Targeting the Mutant Expanded Repeat

Abstract: Friedreich's Ataxia (FA) is an inherited neurologic disorder caused by an expanded GAA repeat within intron 1 of the frataxin (FXN) gene that reduces expression of FXN protein. Agents that increase expression of FXN have the potential to alleviate the disease. We previously reported that duplex RNAs (dsRNAs) and antisense oligonucleotides (ASOs) complementary to the GAA repeat could enhance expression of FXN protein. We now explore the potential of a diverse group of chemically modified dsRNAs and ASOs to defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…Antisense Oligonucleotides (ASOs). ASOs have also been used to increase gene expression in cell lines derived from patients with Friedreich's ataxia and spinal muscular dystrophy [53,54]. The proposed mechanism by which ASOs increase gene expression involves the binding of these compounds to the expanded repeat and blockade of the expanded RNA, which inhibits recognition of DNA, prevents R-loop formation and allows more gene expression.…”
Section: Dna Targeting Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Antisense Oligonucleotides (ASOs). ASOs have also been used to increase gene expression in cell lines derived from patients with Friedreich's ataxia and spinal muscular dystrophy [53,54]. The proposed mechanism by which ASOs increase gene expression involves the binding of these compounds to the expanded repeat and blockade of the expanded RNA, which inhibits recognition of DNA, prevents R-loop formation and allows more gene expression.…”
Section: Dna Targeting Strategiesmentioning
confidence: 99%
“…A study by Li et al [53] demonstrated that ASOs and dsRNAs can activate frataxin protein expression in Friedreich's ataxia patient-derived cell lines that possess varied numbers of GAA repeats. Increased frataxin protein expression was achieved by ASOs incorporating diverse chemical modifications [53].…”
Section: Dna Targeting Strategiesmentioning
confidence: 99%
“…We demonstrated previously that duplex RNAs, singlestranded silencing RNAs (ss-siRNAs), and ASOs can target the expanded GAA repeat, reverse R-loop formation, and cause threefold restoration of FXN protein expression (Li et al 2016(Li et al , 2018. These experiments were performed in patient-derived fibroblast cells.…”
Section: Introductionmentioning
confidence: 99%
“…Given that reduced amount of frataxin is the principal cause of the disease, the main goal of a specific therapy for FRDA is to restore physiological frataxin levels. Several therapeutic approaches under development aim at increasing frataxin levels, using both drug repositioning or drug discovery approaches …”
mentioning
confidence: 99%